Professionalism and Ethics: Is the Tobacco Industry Damaging the Health of the Public Relations Profession? - Khor Yoke Lim; Adnan Hussien (Kajian Malaysia, 2006)
In most parts of the world, public relations (PR) is seeking recognition as a profession. The path to gaining professional status hinges on its adherence to professional ethical standards. This paper argues that it is inappropriate for public relations practitioners to represent the tobacco industry because it is against the PR ethics of upholding truth and public interest. The paper cites historical tobacco industry documents to reveal that the industry would not hesitate to use unethical means to maximise profits.